A clue to unprecedented strategy to HIV eradication: “Lock-in and apoptosis” - Hiroshi Tateishi (Nature Portfolio, 2017)
Abstract Despite the development of antiretroviral therapy against HIV, eradication of the virus from the body, as a means to a cure, remains in progress. A “kick and kill” strategy proposes “kick” of the latent HIV to an active HIV to eventually be “killed”. Latency-reverting agents that can perform the “kick” function are under development and have shown promise. Management of the infected cells not to produce virions after the “kick” step is important to this strategy. Here we show that a newly synthesized compound, L-HIPPO, captures the HIV-1 protein Pr55Gag and intercepts its function to translocate the virus from the cytoplasm to the plasma membrane leading to virion budding. The infecting virus thus “locked-in” subsequently induces apoptosis of the host cells. This “lock-in and apoptosis” approach performed by our novel compound in HIV-infected cells provides a means to bridge the gap between the “kick” and “kill” steps of this eradication strategy. By building upon previous progress in latency reverting agents, our compound appears to provide a promising step toward the goal of HIV eradication from the body.